1998
DOI: 10.1021/np9705165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biological Activities of Triterpenoid Saponins from Maesa lanceolata

Abstract: From a bioassay-guided fractionation procedure using Herpes simplex virus type 1 as the target model, a virucidal saponin mixture (maesasaponin mixture B) was isolated from the MeOH extract of leaves of Maesa lanceolata. The maesasaponin mixture B consisted of six homologous oleanane-type triterpenoid saponins 1-6, identified by 1H, 13C, and 2D NMR spectroscopy and mass spectrometry. The maesasaponin mixture B (1-6) showed several biological activities expected for saponins. It exhibited a moderate virucidal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 22 publications
(55 reference statements)
1
55
0
1
Order By: Relevance
“…The anticancer, antibacterial, fungicidal, and antioxidant activities of C. officinalis L have been frequently attributed to saponins and carotenoids produced by the plant [3,20,22]. Our results suggest that treatment of the marigold plant with SNPs and MeJA can be a good strategy for increasing its medicinal properties.…”
Section: Discussionmentioning
confidence: 70%
“…The anticancer, antibacterial, fungicidal, and antioxidant activities of C. officinalis L have been frequently attributed to saponins and carotenoids produced by the plant [3,20,22]. Our results suggest that treatment of the marigold plant with SNPs and MeJA can be a good strategy for increasing its medicinal properties.…”
Section: Discussionmentioning
confidence: 70%
“…) and 13 C distortionless enhancement polarization transfer (DEPT) NMR data. Its spectral features and physicochemical properties suggested that 1 is a triterpenoid saponin.…”
Section: Resultsmentioning
confidence: 99%
“…Cholesterol and rice bran oil (998) ; cholesterol absorption and aortic fatty streaks (348,358) ; lipid metabolism (999) ; autonomic nervous unbalance and menopausal troubles (climacteric disturbance) (999,1000) ; anti-ulcerogenic (1001) ; antioxidant (357,360,1002) ; gene expression and oxidative stress (1003) ; glycaemia control (1004,1005) ; platelet aggregation (1006) ; anxiety and stress ulcer (1001,1007 -1009) Avenanthramides: Anti-inflammatory and anti-atherogenic (368) ; smooth muscle cell proliferation and NO production (1010,1011) ; antioxidant (140,367,369) Saponins (370,1012,1013) : Hypercholesterolaemia (173,374,377,1014) ; lipase activity and fat absorption (1015) ; transcriptional activity of Cu,Zn-SOD gene (1016) ; scavenger and superoxides (1017) ; hypoglycaemia (1018,1019) ; gastric emptying rate and glucose transport across the brush border of the small intestine (1018,1020) ; antifungal (374) ; anti-viral (1021) ; diabetes (1022) ; anti-inflammatory (1019) ; anti-carcinogenic (374) ; tumour growth and cytostatic effect (1013,1023 -1027) ; bile acid binding (cited in Mimaki et al (1013) ); cell-mediated immune system and antibody production (375)…”
Section: Appendixmentioning
confidence: 99%